Contemplating COVID-19 through disease and death in three short stories by Edgar Allan Poe - Novita Dewi (Universitas Syiah Kuala, 2021)
Wort-case scenarios depicted in literary works may function to mourn and warn people about the real situation, such as the spread of COVID-19 that has altered worldwide life drastically. This study offers a reflection on the current pandemic time through a close reading of selected American classic literary works. The imagination of fear, isolation, and mask-wearing in Edgar Allan Poe’s short stories is resonant with the new expressions of the COVID-19 pandemic. Three short stories by Poe, i.e., ‘The Masque of the Red Death’, ‘The Cask of Amontillado’, and ‘The Sphinx’ are chosen for examination using the thematic analysis method. Repeated reading of the short stories shows that parallels can be drawn between these stories and today’s phenomenon about anxiety, social restriction, and health protocols. What can be implied from the analysis are as follows: (1) Fear of the disease results in the characters’ added distress, (2) The characters’ aberrant behaviour as to overprotect themselves is exacerbated by the dreadful situation, and (3) Poe’s obsession with dread and death to shock the readers can be historically traced through his own inner predicaments, ill-health, and the 1832 Cholera contagion. In conclusion, the findings resonate with the COVID-19 epidemic’s upshots.